A purpose of a new forensic dental identification system for the Military Police of the State of São Paulo based on the INTERPOL's DVI protocol (Research, Society and Development, 2022)
This study aimed to propose a new Dental Forensic Identification System for the Military Police of the State of São Paulo (PMESP) based on the DVI (Identification of Victims of Disasters) protocol of INTERPOL (International Criminal Police Organization). In order to compare the perception about the filling and interpretation, 10 dental officers completed the dental-legal form (FOL) in use currently at the PMESP and the new form based on the INTERPOL’s protocol. A structured questionnaire about the new FOL was also answered by a criminal expert dentist of the Forensic Dentistry Nucleus of the Legal Medicine Institute (IML) of the Superintendence of the Scientific Technical Police (SPTC) of the State of São Paulo. After analyzing the data collected, it was suggested that the new form proposed based on the INTERPOL’s protocol is simpler to complete and easier to interpret than the form currently used, besides being faster and more accurate, meeting internationally accepted parameters. Furthermore, the imaging exam (panoramic radiography) was mentioned as a very important tool in the elaboration of the FOL.